Control de gestión en el proceso de almacenamiento de inmunobiológicos del Ministerio de Salud de Brasil - Fernandes Da Costa, Thiago (2023)
The research aimed to identify the existence of a Management Control System (MCS) and it`s types of control in the immunobiologicals storage process of the National Immunization Program (NIP) from Ministry of Health of Brazil (MoH). Brazilian NIP is one of the largest universal, free-of-charge public health systems in the world. To identify the controls, we used the classification proposed by Kenneth A. Merchant and Wim A. Van der Stede: personnel, action, result and cultural controls. For that, semi-structured interviews carried out with employees and collaborators envolved with storage process of immunobiologicals of the Federal Government of Brazil and, as a result, were identified absence of a formal MCS, as well management controls suitable to manage the risks involved in the process. The study elucidates the relationship between the types of management control of the storage process of immunobiologicals from Federal Government of Brazil. Therefore, allowing future researches relating MCS and the NIP supply chain in Brazil.